Oestrogen levels and humoral immune parameters in Nigerian breast cancer patients (2009)
Objectives: Endocrine and immune interactions mediate breast cancer which is currently incurable. This study attempts at elucidating mechanisms by which breast cancer progresses by determining the levels of oestradiol and humoral immune parameters at different stages of breast cancer compared with women without breast cancer. Patients and Methods: 59 subjects (29 breast cancer attending Surgery Clinics of 2 teaching hospitals in Lagos State, Nigeria and 30 controls) aged 23-82 years were recruited using convenience sampling. Serum was obtained from 10ml of fasting blood from each subject and stored frozen at -20“C until analysis. Oestradiol and albumin were estimated using commercial kits (Adaltis Italia S.P.A and Biolab SA, Maizy, France) respectively. Haptoglobin, alpha-2- macroglobulin, caeruloplasmin, IgG, IgA, IgM were analysed by single radial iinmuno-diffusion method. SPSS version 10 was used for statistical analysis. Main Results: Oestradiol, haptoglobin and caeruloplasmin were significantly increased in premenopausal breast cancer patients compared with premenopausal controls, while only oestradiol was significantly increased in postmenopausal breast cancer patients compared with postmenopausal controls. Moreover, IgM, haptoglobin and caeruloplasmin were significantly reduced in stage III breast cancer patients compared with stages II and IV breast cancer patients. Conclusions: Although inflammation is common to all stages of breast cancer, immunosuppression is most pronounced in breast cancer patients in stage III of the disease.